2019
DOI: 10.1177/0885066619860736
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Norepinephrine Dosage Within 24 Hours as an Indicator of Refractory Septic Shock: A Retrospective Study

Abstract: Background: The management of refractory septic shock remains a major challenge in critical care and its early indicators are not fully understood. We hypothesized that the maximum norepinephrine dosage within 24 hours of intensive care unit (ICU) admission may be a useful indicator of early mortality in patients with septic shock. Methods: In this retrospective single-center observational study, patients with septic shock admitted to the emergency ICU of an academic medical center between April 2011 and March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…Furthermore, the ROC curve and multivariate Cox regression model analyses confirmed that the MDN was an efficient prognostic indicator for mortality in patients with septic shock. This conclusion was in line with the results of a previous study that evaluated 7-day mortality, 11 which was different from the 28-day mortality used in the current study. Combining the results of the previous study and this current study, 11 it can be concluded that the dosage of norepinephrine is a prognostic indicator of both early and late mortality and should be paid close attention to.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Furthermore, the ROC curve and multivariate Cox regression model analyses confirmed that the MDN was an efficient prognostic indicator for mortality in patients with septic shock. This conclusion was in line with the results of a previous study that evaluated 7-day mortality, 11 which was different from the 28-day mortality used in the current study. Combining the results of the previous study and this current study, 11 it can be concluded that the dosage of norepinephrine is a prognostic indicator of both early and late mortality and should be paid close attention to.…”
Section: Discussionsupporting
confidence: 83%
“…This conclusion was in line with the results of a previous study that evaluated 7-day mortality, 11 which was different from the 28-day mortality used in the current study. Combining the results of the previous study and this current study, 11 it can be concluded that the dosage of norepinephrine is a prognostic indicator of both early and late mortality and should be paid close attention to. Furthermore, another study demonstrated that there was no difference in the 28-day mortality by performing a subgroup analysis with a norepinephrine dosage cut-off of 0.04 µg/kg/min.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations